Synthesis of Na2S2O4 mediated cleavable affinity tag for labeling of O-GlcNAc modified proteins via azide-alkyne cycloaddition. (15th September 2021) - Wang, Jiajia; Dou, Biao; Zheng, Lu; Cao, Wei; Zeng, Xueke; Wen, Yinhang; Ma, Jing; Li, Xia
Graphical abstract: Abstract: A facile and convergent procedure for the synthesis of azobenzene-based probe was reported, which could selectively release interested proteins conducted with sodium dithionite. Besides, the cleavage efficiency is closely associated with the structural features, in which an ortho-hydroxyl substituent is necessary for reactivity. In addition, the azobenzene tag applied in the Ac4 GlcNAz-labled proteins demonstrated high efficiency and selectivity in comparison with Biotin-PEG4 -Alkyne, which provides a useful platform for enrichment of any desired bioorthogonal proteomics.